Congress “ROSSTUDSPORT” 2024 (St. Petersburg, ITMO University, December 4–6, 2024) - Makhamedkhanova, Elina A.; Sterlikova, Veronika Y.; Sadovskaya, Sofya S.; Eremina, Ekaterina A. (Физическое воспитание и студенческий спорт)
The paper presents a report on the results of the ROSSTUDSPORT Congress, held at ITMO University from December 4 to 6, 2024 in St. Petersburg.